The Prospects for Greater Enforcement of Teen Employment Laws in Alberta, Canada. “Politically, how do you make it relevant? […] Kill more young people!” - Barnetson, Bob (Relations industrielles / Industrial Relations, 2015)
SummaryThis study uses a Delphi analysis to identify significant barriers to the development of sustained and meaningful pressure on the Alberta government to increase the enforcement of its laws regulating the employment of teenagers. In addition to general employment laws (e.g., wage payment, occupational health and safety) that appear to go broadly unenforced, Alberta also appears not to enforce laws specifying the hours during which teens may work, the occupations in which they may work and the job tasks they may perform. The result is wage theft, workplace injury and illegal forms of employment among teens. The seven Delphi panelists—a mixture of academics, trade unionists and staff members in not-for-profit agencies with an interest in employment matters—identify a tight business-government relationship as an important limit on the political opportunities available to insurgents seeking change. Insurgents must also grapple with a framing that minimizes concerns around teen employment, i.e. by framing illegal or injurious work as an educational rite of passage and complaints as whining. Together, these barriers significantly limit the opportunities to pressure the state to enhance enforcement.Panelists also noted that there is no mobilizing structure in place that teenage workers and their allies can access. Alberta’s labour movement has had limited success organizing the service sector (where most teens are employed). Some panelists suggested leveraging the widespread sexual harassment of female teen workers as a way to access existing networks and resources in feminist and labour organizations. Other panelists argued that focusing on sexual harassment would emphasize individual employers’ misbehaviour and obscure the class-based nature of inadequate enforcement.Most panelists suggested that highlighting the socially inappropriate nature of the death or serious injury of teen workers would be the best way to destabilize the existing barriers to better enforcement of employment laws. The opportunity to do so is (fortunately) rare and may be difficult to leverage. Indeed, research on high profile occupational fatalities in Canada (e.g., the Westray Mine disaster) suggests that such fatalities do not have a significant effect on state enforcement efforts. In the meantime, advocates such as organized labour and community groups may also work to alter conventional views of teen employment by supporting educational or artistic endeavours that problematize teen employment. This could include identifying the risks and consequences of the non-enforcement of laws regulating the employment of teens (such as injury and wage theft) as well as highlighting the reasons why teen workers warrant the enforcement of their workplace rights by the state.